Investigating the Functions of Copper Material Culture from Four Oneota Sites in the Lake Koshkonong Locality of Wisconsin - (:unkn) unknown (My University, 2016)
This thesis explores Oneota use of native copper in the Lake Koshkonong locality between A.D. 1100 and 1400. Over 600 pieces of Oneota copper artifacts originating from four sites were documented and analyzed in order to investigate distribution, production, utilization, and the ideological and social significance behind this raw material. The artifacts analyzed for this study were recovered from Oneota sites adjacent to Lake Koshkonong in Jefferson County, Wisconsin: Crabapple Point (47JE93), Schmeling (47JE833), Koshkonong Creek Village (47JE379), and Crescent Bay Hunt Club (47JE904). These assemblages primarily included awls, beads, pendants, and fragmented material. The data set also includes unique items, such as adzes and a copper mace. Data collected through this project supported multiple conclusions surrounding Lake Koshkonong Oneota copper use. Manufacturing marks on beads provide arguments for multiple manufacturing traditions in the area. The use-wear observed on awls both support and question previous assumptions of their use. Additionally, the distribution of these artifacts among the sites and the iconographic symbols present among the collections suggest larger ideological and social significance of copper within Oneota groups. It also appears that the Lake Koshkonong locality has a prolonged tradition of metalworking that extends from Archaic to Historic period, implying a cultural association with metal production and the physical setting of these sites. Overall, these conclusions suggest that the Oneota viewed copper as a prestige good. These valued items both established and reaffirmed social order and legitimized the ideological, economic, military, and political power of certain individuals or kin groups living along the northwest shores of Lake Koshkonong at this time.
Keywords: Artifact Analysis; Midwest Archaeology; North American Archaeology; Oneota; Prehistoric Copper; Wisconsin Archaeology